Gambaran Status Gizi Penderita Stunting Pada Anak Usia 12-60 Bulan di Wilayah Kerja Puskesmas Tilango - Nur Adyan Mantu; Andi Akifa Sudirman; Dewi Modjo (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Nur Adyan Mantu. Description of nutritional status of stunting sufferers in children aged 12-60 months in the working area of the Tilango Health Center. Guided by Andi Akifa Sudirman as chairman and Dewi Modjo as member. Stunting is a condition where children experience delays in growth caused by lack of nutritional intake for a long time. Good nutritional status is necessary to maintain a degree of fitness and health, aiding growth for the child. The purpose of this study was to determine the nutritional status of stunting sufferers in children in the working area of the Tilango Health Center, Tenggela Village. The design of this study is quantitative descriptive research with. This research was conducted at the Tilango Health Center, Gorontalo Regency. The number of samples was 43 people. The results showed the most BB / U Nutrition Satus, namely Normal weight with 26 respondents (60.5%), the most BB / PB or BB / TB Nutrition Satus, namely Good Nutrition with 37 respondents (86.0%), the most PB / U or TB / U Nutrition Satus, namely Short (Stunting) with 38 respondents (88.4%). The existence of this research is expected to increase and increase maternal knowledge and awareness of the importance of maintaining and maintaining balanced child nutrition to avoid malnutrition.